Crash landing - Avella, Becky (Love inspired suspense., 2017)
When rancher Sean Loomis hires a pilot to help him track a runaway horse on his land, what they find almost gets them killed. Someone has set up an illegal drug smuggling operation on a remote section of Sean's ranch. With their plane shot down and armed thugs who can't leave witnesses hunting them, Sean and brave pilot Deanna Jackson must work together to survive. They narrowly escape but discover they can't trust anyoneincluding law enforcement. With wildfires raging through the area, cutting off communication with the outside world, Sean and Deanna are on their own. Now, to stay alive, they must outwit criminals desperate to see them crash and burn.